2021
DOI: 10.31246/mjn-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between maternal characteristics and stunting in children aged 0 to 23 months in the Philippines

Abstract: Introduction: Stunting is the most prevalent form of child malnutrition worldwide, and is the best overall indicator of growth. This study aimed to determine the relationship between maternal characteristics and nutritional status of children aged 0-23 months based on their length/height-for-age. Method: The study used data from the 2015 Updating Survey conducted by the Philippines’ Food and Nutrition Research Institute – Department of Science and Technology. It employed a stratified multi-stage sampling techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“… 26 , 27 Such tendency is probably due to the challenges that children must deal with during the transition from Exclusive breastfeeding to the consumption of complementary foods. 28 At this time, children will begin to lose passive immunity from their mothers. 29 In addition, there is a possibility of a decrease in nutrition because the frequency of minimum food requirements does not match the child’s age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 Such tendency is probably due to the challenges that children must deal with during the transition from Exclusive breastfeeding to the consumption of complementary foods. 28 At this time, children will begin to lose passive immunity from their mothers. 29 In addition, there is a possibility of a decrease in nutrition because the frequency of minimum food requirements does not match the child’s age.…”
Section: Discussionmentioning
confidence: 99%
“…At the same age, the severity of stunting is more likely to be found in boys. 28 Even among the poorest groups, stunting is more common in boys than in girls. 29 Research carried out in Senegal has found that boys tend to experience failure to thrive due to shorter breastfeeding periods and consuming complementary foods at an earlier age than girls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, of all the predictors, only the predictors of age at first pregnancy and infection were proven to reduce the odds of stunting. It was reported that giving the tetanus vaccine in prenatal care could reduce the odds of stunting by 33% ( 26 ) , and, interestingly, the younger (15-19 years) or older (≥25 years) age at first pregnancy was shown to reduce the odds of stunting events by 63% and 20% respectively ( 14 ) . Regarding the age at first pregnancy, mothers who are ≥25 years old are more likely to live with guaranteed conditions, both in terms of sanitation, socioeconomic, education or urban living areas ( 42 ) , but for the younger age range, further studies may be needed to confirm the results.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the existing predictors, the education of the caregiver, which is the mother, is the predictor that gives the greatest risk of stunting in children 0-24 months. Literature shows that the risk of stunting is significantly greater when the mother has only primary education or even less ( 16 , 27 , 33 - 34 ) , but when the mother has a secondary education level or even college it can reduce the risk or odds of stunting in children ( 26 , 30 ) . With regard to those findings, we consider that the education level of mothers seems to have an indirect effect on stunting ( 32 ) , in which mothers will only be able to provide good quality care to their children, even from pregnancy, if their knowledge is high enough and/ or they understand their child’s nutritional needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation